Unexpected large remnant polarization in Sn-doped Bi4Ti3O ferroelectric film by chemical solution deposition - Y. Zhang; D. P. Song; Z. Z. Hui; H. N. Zhu; J. Yang (Journal of Advanced Dielectrics, 2025)
The A-site rare earth-doped Bi4Ti3O[Formula: see text] (BTO) has been highly interested in nonvolatile ferroelectric random memory devices, piezoelectric devices, electro-optical devices, capacitors, sensors, transducers, etc., due to its low coercive field and superior fatigue resistance properties. However, single B-site doping has not received corresponding attention. In this work, BTO and Bi4Ti[Formula: see text]Sn[Formula: see text]O[Formula: see text] (BTS) thin films were prepared by sol–gel method, in which the doping of Sn effectively restrained the grain growth and decreased the grain size, as well as diminished the formation of oxygen vacancies and enhanced the breakdown field. This leads to a significant enhancement of the ferroelectric properties of the BTO films. The final BTS films exhibit excellent saturation P–E loops with a remnant polarization (2[Formula: see text]) of 94.4[Formula: see text][Formula: see text]C/cm2 and a coercive field (2[Formula: see text]) of 0.69[Formula: see text]MV/cm at a maximum electric field of 2.8[Formula: see text]MV/cm. The ferroelectric fatigue and dielectric properties of BTS film were also characterized. The results suggest that doping of Sn at B-site can effectively improve the breakdown strength and enhance the ferroelectric properties of the BTO film.